THE COMPARATIVE ANALYSES OF THE IMAGE OF AMIR TIMUR IN THE WORKS OF ABDULLA ORIPOV AND CHRISTOPHER MARLOWE - Pulatova Mohichehra Temirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article illustrates the comparative analyzes of the depiction of main hero in “Sohibkhiron” by Abdulla Oripov and “Tamburlaine the Great” by Ch.Marlowe.